2021
DOI: 10.1002/brb3.2448
|View full text |Cite
|
Sign up to set email alerts
|

The Persian version of the centrality of event scale (CES): Assessment of validity and reliability among Iranian university students

Abstract: Background Event centrality, the extent to which an experience is perceived as a central event in one's life, has been found to be a strong correlate of posttraumatic stress disorder (PTSD). The centrality of event scale (CES) is commonly used in different conditions and cultures to measure trauma‐related effects. However, the psychometric properties of this scale have not been investigated in the Iranian context. Methods The present study examined the psychometric properties of the Persian translation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…The 7-item version of this scale has shown good psychometric properties (with alphas between .88 and .93) in related studies (Berntsen & Rubin, 2006;Vermeulen et al, 2020). Recently, the Persian version of the 7-item CES has been validated in Iran and indicated good psychometric properties with Cronbach's alpha of .86 (Azadfar et al, 2022).…”
Section: 23mentioning
confidence: 96%
“…The 7-item version of this scale has shown good psychometric properties (with alphas between .88 and .93) in related studies (Berntsen & Rubin, 2006;Vermeulen et al, 2020). Recently, the Persian version of the 7-item CES has been validated in Iran and indicated good psychometric properties with Cronbach's alpha of .86 (Azadfar et al, 2022).…”
Section: 23mentioning
confidence: 96%
“…This does not necessarily imply that a two-factor solution needs to always be applied when using the CES short form. A unidimensional scale might be sufficient when focusing on a person's most stressful or traumatic life event (e.g., Galán et al, 2017;Vagos et al, 2018;Vermeulen et al, 2020;Azadfar et al, 2022), because for highly stressful or traumatic events, one would expect a relatively similar, strong endorsement of all CES items.…”
Section: Figurementioning
confidence: 99%
“…It is unclear, however, whether other CFA models with more than one factor were tested, because the authors reported results for the single factor solutions only. The same holds for a study conducted by Azadfar et al (2022). These authors tested the unidimensional structure of the CES short form (and only the single factor structure) in a sample of Iranian university students with a history of at least one romantic breakup, on which the CES measure was based on.…”
Section: Introductionmentioning
confidence: 99%
“… 3. Berntsen and Rubin’s concept is event centrality. Some scholars, however, also use the term ‘event centralising’ (see, for example, Azadfar et al, 2022; Broadbridge, 2018). This makes sense because event centralising is the process that individuals actively engage in that gives rise to event centrality. …”
mentioning
confidence: 99%